2020
DOI: 10.1101/2020.07.28.225888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SMAD2 Promotes Myogenin Expression and Terminal Myogenic Differentiation

Abstract: SMAD2 is a transcription factor whose activity is regulated by members of the Transforming Growth Factor beta (TGFβ) superfamily. While activation of SMAD2 and SMAD3 downstream of TGFβ or myostatin signaling is known to inhibit myogenesis, we find that SMAD2 in the absence of TGFβ signaling promotes terminal myogenic differentiation. We find that during myogenic differentiation, SMAD2 expression is induced. Knockout of SMAD2 expression in primary myoblasts did not affect the efficiency of myogenic differentiat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Upon activation of their receptors by members of the TGFβ superfamily, Smad4 forms heterodimers with one of the five R-Smads in the cytosol and together they are translocated to the nucleus to bind to their target genes ( Massagué, 2008 ). The function of SMADs, including SMAD4, has been studied in the processes of myoblast proliferation and differentiation ( Yanagisawa et al, 2011 ; Ono et al, 2011 ; Cohen et al, 2015 ; Lamarche et al, 2020 ; Paris et al, 2016 ; Stantzou et al, 2017 ). Nevertheless, whether and how the SMADs proteins causally regulate MuSC self-renewal was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation of their receptors by members of the TGFβ superfamily, Smad4 forms heterodimers with one of the five R-Smads in the cytosol and together they are translocated to the nucleus to bind to their target genes ( Massagué, 2008 ). The function of SMADs, including SMAD4, has been studied in the processes of myoblast proliferation and differentiation ( Yanagisawa et al, 2011 ; Ono et al, 2011 ; Cohen et al, 2015 ; Lamarche et al, 2020 ; Paris et al, 2016 ; Stantzou et al, 2017 ). Nevertheless, whether and how the SMADs proteins causally regulate MuSC self-renewal was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Among the eight known Smad proteins in mammals, Smad4 is unique in that it functions as an indispensable Co-Smad for five R-Smads (receptor-regulated Smads, i.e., Smad1, 2, 3, 5, and 8): upon activation of their receptors by members of the TGFβ superfamily, Smad4 forms heterodimers with one of the five R-Smads in the cytosol and together they are translocated to the nucleus to bind to their target genes 48 . The function of SMADs, including SMAD4, has been studied in the processes of myoblast proliferation and differentiation [49][50][51][52][53][54] . Nevertheless, whether and how the SMADs proteins causally regulates MuSC self-renewal was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the expression of TGFBR3 protein coincides with the decreased SMAD2/3 activity, indicated by less enriched binding motif of SMAD2/3 in the open chromatin sequences of the selfrenewing population. Although activation of SMAD2/3 via TGFβ or myostatin signaling inhibits myogenesis 55,56 , recent studies reported that SMAD2 and SMAD3 can promote myogenic differentiation independent of TGFβ signaling 52,[57][58][59] . Particularly, SMAD2 is identified as an important positive regulator of myogenic differentiation by driving Myog expression 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because features, structure, and nutrient content, such as proteins, fatty acids, and vitamins, are signi cantly impacted by cell maturity, the maturity degree of the produced nal cells is a critical assessment criterion at this stage (Wuyi, 2019). Although muscle stem cells are thought to have a high potential for myogenic differentiation, the diameter, length, and protein content of ex vivo generated myo bers vary considerably depending on the culture conditions and may be substantially lower than actual muscle bers (Braga et al, 2017;Lamarche et al, 2021;Park et al, 2016).…”
Section: Differentiation Of Cellmentioning
confidence: 99%